ASPEK SANITASI DAN HIGIENE DI KANTIN ASRAMA TINGKAT PERSIAPAN BERSAMA (TPB) INSTITUT PERTANIAN BOGOR - Evy Damayanthi; Lilik Nur Yuliati; Vitriani Y. Suprapti; Fitriana Sari (Jurnal Gizi dan Pangan, 2008)
The major purpose of this research was to analyze sanitation and hygiene at TPB - IPB Dormitory’s Canteens. Microbiological analysis (sanitation analysis) was done on chef’s hands and some utensils (eating plate, serving plate, and chopping board). There were a lot of Staphylococcusfound in food handler’s hands (19-57 CFU). This research showed that there was no tendency which was the worst canteen from the three canteens at boy’s dormitory or girl’s dormitory. The statistical analysis showed that the location of the canteen and kind of utensils influenced the total Enterobacter. The chef’s hands of C1 and A3 canteens contained E. coli bacteria, but the other chef’s hands, did not. Eating plate, serving plate, and chopping board from Canteens A3 and C1 were not safe due to the number of microbes they had (1.08x102-3.6x102 CFU/cm2). All utensils at canteen A1 were safe. C2’s and C3’s chopping boards were not safe, but their eating plate and serving plate were safe.